The definition of Corporate Social Responsibility in China - Goto, Kyoko (2007)
Corporate Social Responsibility (CSR) is beginning to gain attention from businessmen, academics and other non-business individuals as it is becoming increasingly important for corporations to perform their business in a socially responsible manner. It is important nowadays to adopt CSR because various stakeholder groups, crucial to a corporations business, are expressing concerns about the social and environmental impact a business has. At present, with numerous environmental problems such as global warming due to high energy consumptions and social problems such as cheap wages for employees working under hazardous conditions, business that may worsen such problems are not considered sustainable. Therefore corporations are beginning to adopt CSR.